KOMUNIKASI PARTISIPATIF KELOMPOK SADAR WISATA THE CARETAKER DALAM MENGEMBANGKAN WISATA SAMUDERA AWAN BUKIT SULIGI DI ROKAN HULU - Nursanti "; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The tourism sector now becomes a leading sector of development because of it able to touch the lowest level of community with a share economy and increasing performance. Tourism development requires participation from communities around tourist areas to develop and advance a tourist attraction. The presence of Pokdarwis or tourism conscious groups is a way to attract community participation. It is The Caretaker who is considered successful in managing and developing the tourism of Samudera Awan Bukit Suligi in Rokan Hulu. This study aims to find out how kinds of participatory communication, kinds of coaching and participative communication models of The Caretaker in developing the Samudera Awan Bukit Suligi tourism in Rokan Hulu.This study uses qualitative research methods with a participatory model. The research subjects were eleven informants who were selected using a purposive technique. Data collected by in-depth interviews, observation, and documentation. And data validation uses the technique of extending participation, perseverance observation, and triangulation. The results of this study showed that participative communication conducted by The Caretaker group in developing the Samudera Awan Bukit Suligi tourism was carried out through internal and external discussions or meetings. The kinds of participatory communication consist of three stages, which is the planning, implementation, and utilization of results. The kind of guidance consists of two kinds, directly or indirectly guidance. Directly guidance is given through discussion, training, and socialization; while indirectly guidance is given through books and Instagram accounts (social media). For the communication model used is two - way participatory communication model. This model is applied in the form of meetings or discussions. Keywords: The Caretaker, Pokdarwis, Participatory Communication, Touri